Sejarah dan Karakteristik Budaya Papua Perspektif Pendidikan Islam - B, Jumrana; Jahra; Zakaria, Maghfirah; Abdillah M., Fardan; Nur, Indria; Ahriani, Andi (Tasamuh: Jurnal Studi Islam, 2026)
This study examines the integration of history and cultural characteristics of Papua from an Islamic education perspective, exploring the application of cultural values through the traditions of Sasi, Satu Tungku Tiga Batu, and Bakar Batu within the religious education system in Papua. It also identifies challenges in developing Islamic education suited to Papua's unique social and cultural context. A qualitative approach was employed, utilizing in-depth interviews, participant observation, and case studies. Data were gathered from religious leaders, traditional leaders, religious teachers, and local communities to understand the relationship between Islamic education and local culture. Findings reveal that Islamic education in Papua has successfully integrated local cultural values with Islamic teachings. The Sasi tradition, which promotes sustainable environmental management, aligns with Islamic principles of preserving the earth. The Satu Tungku Tiga Batu principle, representing the balance among custom, religion, and society, serves as a foundation for teachings on cooperation and cultural respect. Meanwhile, the Bakar Batu tradition, which emphasizes social solidarity, reflects Islamic values of mutual assistance and communal togetherness. Despite these successes, Islamic education in Papua faces significant challenges, particularly limited access in remote areas. Inadequate infrastructure and a shortage of qualified teaching staff hinder the delivery of quality education. To address these issues, the study recommends integrating educational technology and reforming the curriculum to better meet the needs of the Papuan people. Overall, Islamic education in Papua plays a vital role in bridging religious teachings with local culture, fostering a more balanced, knowledgeable, and morally grounded society.